Molecular Approaches to Genetic Diversity - Caliskan, Mahmut; Cevahir Oz, Guul; Halil Kavakli, I.; Ozcan, Birguul (IntechOpen, 2015)
In the last 50 years, combinations of conventional and molecular methods have made the genetic diversity a widespread science. Moreover, the issue of conserving genetic diversity as a component of the conservation of the environment has been raised at an international level. We hope that the current book will provide a glimpse into the dynamic process of genetic diversity by presenting the research of some of the scientists who are engaged in development of new tools and ideas in genetic diversity. We would like to express our deepest gratitude to all authors who contributed to this book by sharing their valuable works with us.